At Europe's edge: migration and crisis in the Mediterranean - Mainwaring, Ċetta (Oxford scholarship online Political Science, 2019)
The Mediterranean Sea is now the deadliest region in the world for migrants. Although the death toll has been rising for many years, the EU response remains fragmented and short sighted. Politicians frame these migration flows as an unprecedented crisis and emphasize migration control at the EU's external boundaries. In this context, 'At Europe's Edge' investigates why the EU prioritizes the fortification of its external borders; why migrants nevertheless continue to cross the Mediterranean and to die at sea; and how EU member states on the southern periphery respond to their new role as migration gatekeepers. This work addresses these questions by examining the relationship between the EU and Malta, a small state with an outsized role in migration politics as EU policies place it at the crosshairs of migration flows and controls.